Padrão respiratório ineficaz em crianças com cardiopatias congênitas: construção e validação por juízes de uma teoria de médio alcance - Souza, Nayana Maria Gomes (2017)
To understand the dynamics of the ineffective breathing pattern in children with congenital heart disease, it is necessary to deepen the study around its causal factors, essential attributes and clinical indicators, besides understand how they relate to each other. A useful tool to perform this type of analysis is the Middle Range Theory (MRT). Therefore, this study aims to verify the validity of the structure of nursing diagnosis Ineffective breathing pattern (IBP) in children with congenital heart defects by performing two steps: construction of a middle range theory and analysis by experts. The first step of the study was developed based on the model proposed by Lopes, Silva and Herdman (2015). The construction of the Middle range Theory for the nursing diagnosis Ineffective breathing pattern in children with congenital heart defects was based on the Roy Adaptation Model (MAR), an integrative review of the literature and the taxonomy of NANDA International, Inc. (NANDA-I). The integrative review was accomplished by means of an extensive literature search from four databases (SCOPUS, CINAHL, PUBMED and Web of Science). After applying the inclusion and exclusion criteria, 50 studies were selected that supported the construction of the middle range theory. After reading and analyzing the theoretical references, 10 stimuli of the IBP diagnosis were identified, of which six do not correspond to the related factors reported in NANDA-I; 21 behaviors were found, of which five are not included in the list of NANDA-I defining characteristics. Stimuli and behaviors were incorporated into the diagnosis structure. Conceptual and operational definitions were then developed for each stimulus and behavior. Were described propositions that explain the relationship between IBP and its structural components, as well as establishing the causal relationships of the diagnosis. To synthesize propositions and causal relationships, a pictogram was created. The second step of the present study counted on the participation by 23 experts in nursing terminology and / or clinical practice. They judged the stimuli and behaviors of the MRT, as well as their conceptual and operational definitions based on the criteria of relevance, clarity and precision. The final proposal of the validation process incorporates nine stimuli: increase in airway resistance, reduction of lung compliance, increase in carbon dioxide concentration, increase in hydrogen concentration, position of the body that inhibits lung expansion, chest wall deformities, physical effort, anxiety and pain. With respect to the behaviors, all were considered as relevant: use of accessory muscles for breathing, alterations in respiratory depth, tachypnea, changes in respiratory rhythm, dyspnoea, orthopnea, hypoxia, hypoxemia, cyanosis, sleep respiratory disorders, respiratory muscle fatigue, prolonged expiratory phase, bradypnoea, altered thoracic excursion, decreased expiratory pressure, decreased inspiratory pressure, decreased minute- ventilation, pursed lip breathing, increased anteroposterior diameter, and assuming a three-point position. With the exception of the stimulus age less than two years, the conceptual and operational definitions constructed for the stimuli and the behaviors presented index of validity of diagnostic content superiors to 0.9. It is considered that the process of validation of the structure of nursing diagnosis Ineffective Respiratory Standard (PRI) in children with congenital heart diseases subsidized the refinement and improvement of this diagnosis and its components. It is indispensable e for nursing to appropriate this diagnosis in the context of the care of the child with congenital heart disease. It is suggested that a clinical validation study be conducted to evaluate the components of PRI not yet incorporated into NANDA-I, as well as to verify the validity of the propositions and causal relationships pointed out in the TMA.